Nilai Tukar Mata Uang, Inflasi Dan Pengaruhnya Terhadap Harga Pasar Di Indonesia Pada Masa Pandemi Covid 19 - Anhar Nurdiansyah Harahap; Humaidi Sitompul (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
Anhar Nurdiansyah Harahap1, Humaidi Sitompul2Ekonomi Islam/ S1/ Fakultas Ekonomi Dan Bisnis Islam/ Universitas Islam Negeri Sumatera Utara/ Medan/ Indonesia.ABSTRACT This research was conducted to obtain information related to currency exchange rates during the COVID-19 pandemic which affected many aspects, especially in the economy. The effect on market prices caused by inflation that occurs in the pandemic scheme is the content in the journal made by the author. This research is a quantitative research using secondary data obtained from BI and BPS. The data to be obtained is related to the prices of basic commodities in Indonesia area affected by the pandemic which has caused market prices to increase or decrease. The research method is by collecting data on the prices of basic commodities that are already in the data by BI and BPS. As a result, we will find out how currency exchange rates, inflation, and the effect on market prices during the pandemic in Indonesia . And to be able to find the root of the problem and the solution to create a stable market price.Keywords:Currency exchange rates; inflation; the market price of basic commodities; pandemic